Neoadjuvant Cabozantinib in an Unresectable Locally Advanced Renal Cell Carcinoma Patient Leads to Downsizing of Tumor Enabling Surgical Resection: A Case Report - Bilen, Mehmet A.; Jiang, James F.; Jansen, Caroline S.; Brown, Jacqueline T.; Harik, Lara R.; Sekhar, Aarti; Kissick, Haydn; Maithel, Shishir K.; Kucuk, Omer; Carthon, Bradley; Master, Viraj A. (Frontiers in Oncology, 2021)
Introduction Cabozantinib (XL-184) is a small molecule inhibitor of the tyrosine kinases c-Met, AXL, and VEGFR2 that has been shown to reduce tumor growth, metastasis, and angiogenesis. After the promising results from the METEOR and CABOSUN trials, cabozantinib was approved for use in the first- and second-line setting in patients with advanced RCC. Previously, targeted therapies have been used in the neoadjuvant setting for tumor size reduction and facilitating nephrectomies. The increased response rates with cabozantinib in metastatic renal cell carcinoma (mRCC), along with the other neoadjuvant TKI data, strongly support an expanded role for cabozantinib in the neoadjuvant setting. Case Description We report on a 59-year-old gentleman presenting with an unresectable 21.7 cm left renal cell carcinoma (RCC) with extension to soft tissue and muscles of the thoracic cage, psoas muscle, posterior abdominal wall, tail of pancreas, splenic flexure of colon, and inferior margin of spleen. Presurgical, neoadjuvant systemic therapy with cabozantinib was initiated for 11 months in total. Initially after 2 months of cabozantinib, magnetic resonance imaging (MRI) revealed a significant reduction (44.2%) in tumor diameter from 21.7 to 12.1 cm with decreased extension into adjacent structures. After 11 months total of cabozantinib, the corresponding MRI showed grossly stable size of the tumor and significant resolution of invasion of adjacent structures. After washout of cabozantinib, radical resection, including nephrectomy, was successfully performed without any major complications, either intra-operative or perioperative. Negative margins were achieved. Conclusions This is a report of neoadjuvant cabozantinib downsizing a tumor and enabling surgical resection in this patient with locally advanced RCC. Our findings demonstrate that neoadjuvant cabozantinib to facilitate subsequent surgical resection may be a feasible option for patients presenting with unresectable RCC.